Critical Success Factors for Knowledge Transfer via an Australian Government Education Website - Azizan, N; Smith, R; Cooper, V (Int Business Information Management Assoc-Ibima, 2024)
The transfer of knowledge pertaining to government services is central to the success of e-government websites. This paper explores critical success factors (CSFs) for the transfer of knowledge from government to users (citizens, business entities, employees and other government agencies) via an Australian government education website, from the perspective of the government website provider. CSFs are defined as "the limited number of areas in which results, if satisfactory, will ensure successful competitive performance for the organization" (Rockart 1979, p. 5). It has been recognized that there are generally a small number of such attributes that, if performed well, will create opportunities for success (King 2001). Knowledge transfer (KT) is defined as a process that includes "any exchange of knowledge between or among individuals, teams, groups or organizations" (King 2006, p. 538). It is the process by which knowledge is transmitted to and absorbed by users. Knowledge in this research is scoped to include government knowledge resources (information and services) made explicit and available to users via government websites. The research has adapted Szulanski's KT four stages model as a lens to study CSFs. The research has employed an interpretive case study approach, applying qualitative data capture and analysis methods. Eleven CSFs are identified and grouped into six themes. The research provides guidance to practitioners, arguing that identifying and understanding the CSFs can support government website providers in taking decisions related to the internal operation of their website's content development and delivery activities, so enhancing their capacity to deliver requisite knowledge to website users.